Hubungan Pijat Oksitosin Dengaln Kelancaran Pengeluaran Asi pada Ibu Postpartum di Kelurahan Tomuan Kecamatan Siantar Timur Kabupaten Simalungun Tahun 2023 - Mei Tri Janti Silalahi; Sri Rezeki (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
According to data from the Indonesian Ministry of Health in 2021, the presentation of exclusive breastfeeding to infants showed an improvement from the previous year, from 69.62% to 71.58%. However, most provinces have a percentage below the national average, including Gorontalo (52.75%), Central Kalimantan (55.98%), West Papua (58.77%), Riau Islands (58.84%), DKI Jakarta 65.63%, Aceh (66.66%) and North Sumatra (57.83%). (Monavia, 2021). This study aims to identify the relationship between oxytocin massage and smooth breastfeeding for postpartum mothers in Tomuan Village, Siantar Timur District, Simalungun Regency in 2023.Type of quantitative research with cross sectional design. This study was conducted on a sample of 20 postpartum. To measure the characteristics of the respondents used a data collection form, to measure oxytocin massage with the smooth expulsion of breast milk in postpartum mothers respondents used a questionnaire.Based on the relationship between oxytocin massage and smooth breastfeeding in postpartum mothers, a p-value of 0.000 (p<0.05) was obtained which indicated that there was a significant relationship between oxytocin massage and smooth breastfeeding in postpartum mothers in Tomuan Village, Siantar Timur District, Simalungun Regency . Thus Ho is rejected, the correlation strength (r) = 0.014.The relationship between oxytocin massage and the smoothness of breastfeeding in postpartum mothers in the Tomuan Village, Siantar Timur District, Simalungun Regency, a category that has done oxytocin massage. It is recommended for postpartum mothers to do oxytine massage optimally so that breastfeeding can flow smoothly in Tomuan Village, East Siantar District, Simalungun Regency